KINERJA KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI MADRASAH ALIYAH MAHDALIYAH KOTA JAMBI - Kartini, Eva; Putra, Darma (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2024)
The professional quality of a teacher is reflected in their responsibility to guide and teach students using their experiences, both within and outside the school environment, with the intention of fostering the development of intelligent individuals with good morality. This article aims to explore the role and performance of school principals in enhancing the professional competence of teachers in Madrasah Aliyah Mahdaliyah in the city of Jambi. This research employs a qualitative method with a case study approach. Data were gathered through in-depth interviews with school principals, direct observation, and analysis of relevant documents. Findings indicate that school principals play a significant role in developing the professional competence of teachers through various strategies, including the development of training programs, effective supervision, and providing adequate support. Additionally, internal and external factors also influence the performance of school principals in efforts to enhance teacher competence. The implications of these findings underscore the importance of the role of school principals in creating an environment supportive of teacher professional growth to improve the quality of education in Madrasah Aliyah Mahdaliyah